2014
DOI: 10.1016/j.joca.2014.01.010
|View full text |Cite
|
Sign up to set email alerts
|

Bone sialoprotein as a potential key factor implicated in the pathophysiology of osteoarthritis

Abstract: This study supports the implication of BSP in the pathology of OA and suggests that it could be a key mediator of the hypertrophic chondrocytes-induced angiogenesis. To control chondrocyte hypertrophic differentiation is promising in the treatment of OA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 51 publications
(36 reference statements)
1
19
0
Order By: Relevance
“…However, it is not certain that this finding could explain the observation of this study [36]. Other studies suggested that bone biomarkers like osteopontin and bone sialoprotein are more relevant in the pathogenesis of osteoarthritis [37]. Studies also found that CTX-II correlated better with disease progression of osteoarthritis [38,39].…”
Section: Discussionmentioning
confidence: 54%
“…However, it is not certain that this finding could explain the observation of this study [36]. Other studies suggested that bone biomarkers like osteopontin and bone sialoprotein are more relevant in the pathogenesis of osteoarthritis [37]. Studies also found that CTX-II correlated better with disease progression of osteoarthritis [38,39].…”
Section: Discussionmentioning
confidence: 54%
“…This was evidenced through reduced GAG loss accompanied by decreased COL10A1 staining (Eswaramoorthy et al, 2012 ). The anti-hypertrophic role of PTHrP signaling was further confirmed in a study in which OA chondrocytes incorporated in alginate beads were treated with PTHrP, leading to reduced COL10A1 expression (Pesesse et al, 2014 ).…”
Section: Resultsmentioning
confidence: 84%
“…The importance of angiogenesis in OA is now well known. Blood vessels have been observed in OA cartilage and an overexpression of pro-angiogenic factors by OA chondrocytes was demonstrated [ 37 39 ]. Data generated in the present microarray showed that various key mediators of angiogenesis were modulated by IL-1β and COT.…”
Section: Discussionmentioning
confidence: 99%